Mutual fund board connections and proxy voting - Calluzzo, Paul; Kedia, Simi (Journal of Financial Economics, 2019)
We study fund-firm connections that arise when firm executives and directors serve as fund directors. We find that connected funds are significantly more likely to vote with management in proposals with negative Institutional Shareholder Services (ISS) recommendations or low shareholder support. As our data show that management support does not exist either before connection formation or after its termination, this result is unlikely to be caused by omitted factors. Rather, the connected fund's voting patterns show independence from ISS recommendations and successful connected voting is associated with positive announcement returns, suggesting that connected fund support for management reflects information advantages. Lastly, we find that a fund family and firm are more likely to connect when the fund family holds a large stake in the firm and is geographically proximate as well as when it has a record of voting independently from ISS.